RELEVANSI BUDAYA PATRIARKI DENGAN BIROKRASI PEMERINTAHAN PADA DINAS PERHUBUNGAN KOTA MAKASSAR - Kartini Kharisma Nur; Jaelan Usman; Ihyani Malik (Program Magister Ilmu Administrasi Publik, Universitas Muhammadiyah Makassar, 2022)
This study purposed to analyze the relevance of patriarchal culture with government bureaucracy. This study used qualitative by using direct interviews with related informants and this study used descriptive qualitative, namely providing an overview based on phenomena and facts that occured. The results of this study showed there was a relevance of patriarchal culture with the government bureaucracy at the Makassar City Transportation Service which in essence patriarchy meant that the highest power was in men. This was evident in the ideology based on the dominant temperament, which was male employees who occupied the most structural positions. But for patriarchal ideology based on sex roles and status, women were essentially also able to enter the world of bureaucracy. Women were no longer a domestic service or household work but also they were able to become women career to survive their live, and their political status could also complete with men according to their hierarchical structure and career path without distinguishing gender, race, and religion.